Kepuasan Kerja dengan Employee Engagement pada Driver Ojek Online - Dicky Sidarius Halias; Sowanya Ardi Prahara (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to determine the relationship between job satisfaction with employee engagement on online motorcycle taxi drivers who work in Yogyakarta. The hypothesis in this study is that there is a positive relationship between job satisfaction with employee engagement on online motorcycle taxi drivers who work in Yogyakarta. The research subjects were online motorcycle taxi drivers who had worked for at least 3 months totaling 82 people. Taking the subject using purporsive sampling with data collected using the Employee Engagement Scale and Job Satisfaction Scale. Data were analyzed using product moment correlation. Based on the analysis, a correlation value of 0.544 was obtained with p = 0.000 (p <0.005). These results indicate that there is a significant positive relationship between job satisfaction with employee engagement on online motorcycle taxi drivers who work in Yogyakarta. This means that the higher job satisfaction of online motorcycle taxi drivers, the higher the employee engagement of motorcycle taxi drivers online, conversely, the lower the job satisfaction, the lower the employee engagement.